Nonredundant Roles of Platelet Glycoprotein VI and Integrin αIIbβ3 in Fibrin-Mediated Microthrombus Formation. Issue 2 (February 2021) - Perrella, Gina; Huang, Jingnan; Provenzale, Isabella; Swieringa, Frauke; Heubel-Moenen, Floor C.J.I.; Farndale, Richard W.; Roest, Mark; van der Meijden, Paola E.J.; Thomas, Mark; Ariëns, Robert A.S.; Jandrot-Perrus, Martine; Watson, Steve P.; et al.
Abstract : Objective: Fibrin is considered to strengthen thrombus formation via integrin αIIbβ3, but recent findings indicate that fibrin can also act as ligand for platelet glycoprotein VI. Approach and Results: To investigate the thrombus-forming potential of fibrin and the roles of platelet receptors herein, we generated a range of immobilized fibrin surfaces, some of which were cross-linked with factor XIIIa and contained VWF-BP (von Willebrand factor-binding peptide). Multicolor microfluidics assays with whole-blood flowed at high shear rate (1000 s −1 ) indicated that the fibrin surfaces, regardless of the presence of factor XIIIa or VWF-BP, supported platelet adhesion and activation (P-selectin expression), but only microthrombi were formed consisting of bilayers of platelets. Fibrinogen surfaces produced similar microthrombi. Markedly, tiggering of coagulation with tissue factor or blocking of thrombin no more than moderately affected the fibrin-induced microthrombus formation. Absence of αIIbβ3 in Glanzmann thrombasthenia annulled platelet adhesion. Blocking of glycoprotein VI with Fab 9O12 substantially, but incompletely reduced platelet secretion, Ca 2+ signaling and aggregation, while inhibition of Syk further reduced these responses. In platelet suspension, glycoprotein VI blockage or Syk inhibition prevented fibrin-induced platelet aggregation. Microthrombi on fibrin surfaces triggered only minimal thrombin generation, in spite of thrombin binding to the fibrin fibers. Conclusions: Together, these results indicate that fibrin fibers, regardless of their way of formation, act as a consolidating surface in microthrombus formation via nonredundant roles of platelet glycoprotein VI and integrin αIIbβ3 through signaling via Syk and low-level Ca 2+ rises. Abstract : Supplemental Digital Content is available in the text.